Classroom Support for the Newcomers to UK Mainstream Schools - Abdelbasit Gadour; Samia Amniana (Britain International for Academic Research (BIAR) Publisher, 2010)
The quest of English language learners to attain proficiency in English has been a phenomenon that needs to be investigated, particularly in relation to changes in UK national educational policy and funding that has defused the needs of EAL learners within a more general emphasis on inclusion and raising the achievement of ethnic minority children. Qualitative methods are used to allow thirteen children from Libya (newcomers) along with their parents and teachers to talk about their experiences of classroom support available for EAL learners within UK mainstream schools. Data are analysed using thematic analysis. The results showed that there is a lack of provision to enable teachers meet the specific language needs of EAL children. In fact, Libyan children found themselves immersed in a new classroom without EAL support or clear instructions through their first language. It was simply up to them whether they sank or swam. The implications of this study suggest that there is a need for careful assessment of EAL children’s academic background and level of primary language literacy. This should be derived from long-term procedures based on a structured national educational policy to respond to the newly-arrived EAL children and help them settle into mainstream schools.